2005
DOI: 10.1002/aic.10664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on synthesis and properties of perovskite oxide via a citrate process

Abstract: O 3-␦ (LSCF) perovskite-type oxides were synthesized using a modified citrate process under various pH conditions (pH ϭ1, 3, 5, 7, and 9, respectively). The effect of pH on the chelate process, crystal development, morphology, and oxygen permeability of LSCF oxides were investigated. FT-IR analysis showed that the chelate processes for pH ϭ 1 and 3 were different from those for pH ϭ 5, 7, and 9. (pH ϭ 5, 7, and 9) in the range of 1073-1123K. This study indicated that properties such as crystallinity and oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The Pechini method, based on single EDTA or citric acid complexing process, was found to be influenced by pH, even though this impact is much less sensitive compared to that of the sol-gel method with metal alkoxides [34]. Figure 3 shows the XRD patterns of GCBCO powders from different pH-valued precursors calcined at 850°C for 10 h. It was observed that the EDTA-citrate process was relatively pH insensitive.…”
Section: Effect Of the Different Ph-valued Precursorsmentioning
confidence: 96%
“…The Pechini method, based on single EDTA or citric acid complexing process, was found to be influenced by pH, even though this impact is much less sensitive compared to that of the sol-gel method with metal alkoxides [34]. Figure 3 shows the XRD patterns of GCBCO powders from different pH-valued precursors calcined at 850°C for 10 h. It was observed that the EDTA-citrate process was relatively pH insensitive.…”
Section: Effect Of the Different Ph-valued Precursorsmentioning
confidence: 96%
“…12 A dry-pressing technique 4 was used to prepare the supported dense mixed-conducting membranes (see supporting information, S1). Membrane reactor configuration and experimental procedures for POM reaction are similar to the previous ones reported by our laboratory (S2).…”
Section: Methodsmentioning
confidence: 99%
“…Differences in experimental details, such as the gas atmosphere which modifies the membrane surface (Yi et al, 2005;Arnold et al, 2007), the sealing material (Qiu et al, 1995) and the difference in preparation procedure (Kharton et al, 2001;Qi et al, 2000;Wu et al, 2006;Zhang et al, 1999) have been suggested to account for such discrepancies. Yi et al (2005) found that the co-presence of CO 2 and H 2 O in air had profound effects on the phase composition, microstructure, and oxygen permeability of a Sr 0.95 Co 0.8 Fe 0.23− membrane, and attributed these effects to the formation of bicarbonate on the membrane surface.…”
Section: Introductionmentioning
confidence: 95%